Reduction of lithium induced interstitial fibrosis on co-administration with amiloride - Mehta, Paulomi M.; Gimenez, Gregory; Walker, Robert J.; Slatter, Tania L. (Scientific reports, 2022)
Long-term administration of lithium is associated with chronic interstitial fibrosis that is partially reduced with exposure to amiloride. We examined potential pathways of how amiloride may reduce interstitial fibrosis. Amiloride was administered to a rat model of lithium induced interstitial fibrosis over a long term (6 months), as well as for short terms of 14 and 28 days. Kidney cortical tissue was subjected to RNA sequencing and microRNA expression analysis. Gene expression changes of interest were confirmed using immunohistochemistry on kidney tissue. Pathways identified by RNA sequencing of kidney tissue were related to ‘promoting inflammation’ for lithium and ‘reducing inflammation’ for amiloride. Validation of candidate genes found amiloride reduced inflammatory components induced by lithium including NF-κB/p65 Ser536 and activated pAKT Ser473 , and increased p53 mediated regulatory function through increased p21 in damaged tubular epithelial cells. Amiloride also reduced the amount of Notch1 positive PDGFrβ pericytes and infiltrating CD3 cells in the interstitium. Thus, amiloride attenuates a multitude of pro-inflammatory components induced by lithium. This suggests amiloride could be repurposed as a possible anti-inflammatory, anti-fibrotic agent to prevent or reduce the development of chronic interstitial fibrosis.